Answer:
a. m∠1 = 75°
b. m∠2 = 46°
c. m∠3 = 59°
d. m∠4 = 59°
e. m∠5 = 46°
f. m∠7 = 121°
g. m∠8 = 59°
h. m∠9 = 62°
i. m∠10 = 118°
j. m∠11 = 59°
k. m∠13 = 118°
i. m∠14 = 62°5
Example 5
m∠1 =78°
m∠2 = 102°
m∠3 = 59°
m∠4 = 102°
m∠5 = 38
m∠6 = 142°
m∠7 = 38°
m∠8 = 142°
m∠9 = 78°
m∠11 = 78°
m∠12 = 102°
m∠13 = 38°
m∠14 = 142°
Explanation:
a. m∠1 ≅ m∠6 (Alternate angle theorem)
m∠1 = m∠6 = 75° (Definition of congruency)
m∠1 = 75°
b. m∠12 = m∠5 + m∠6 (Angle addition postulate/Corresponding angles)
m∠5 = 121° - 75° = 46°
m∠5 = 46°
m∠2 ≅ m∠5 (Alternate angle theorem)
m∠2 = m∠5 = 46° (Definition of congruency)
m∠2 = 46°
c. m∠3 = 180 - (m∠1 + m∠2) (Angle subtraction and sum of angles on a straight line)
m∠3 = 180 - (75 + 46) = 59°
m∠3 = 59°
d. m∠4 = 180 - (m∠1 + m∠5)
m∠4 = 180 - (75 + 46) = 59°
m∠4 = 59°
e. m∠12 = m∠5 + m∠6 (Angle addition postulate/Corresponding angles)
m∠5 = 121° - 75° = 46°
m∠5 = 46°
f. m∠7 = m∠12 = 121° (Alternate angle theorem)
m∠7 = 121°
g. m∠8 = 180 - m∠7 = 180 - 121 = 59°
m∠8 = 59°
h. m∠9 + m∠5 + m∠8 = 180 (The sum of the interior angles of a triangle)
m∠9 = 180 - (59 + 59) = 62°
m∠9 = 62°
i. m∠10 = 180 - m∠9 = 180 - 62 = 118°
m∠10 = 118°
j. m∠11 = m∠8 = 59°
m∠11 = 59°
k. m∠13 = m∠10 = 118°
m∠13 = 118°
i. m∠14 = m∠9 = 62°
m∠14 = 62°
Example 5
m∠5 = m∠7 = 38
m∠5 = 38°
m∠6 = 180 - 38 = 142°
m∠6 = 142°
m∠8 = m∠6 = 142°
m∠8 = 142°
m∠12 = m∠10 = 102°
m∠12 = 102°
m∠11 = 180 - m∠12 = 180 - 102 = 78°
m∠11 = 78°
m∠9 = m∠11 = 78°
m∠9 = 78°
m∠1 = m∠9 = 78°
m∠1 =78°
m∠3 = 78°
m∠2 = m∠4 = m∠10 = 102°
m∠13 = 360 - (m∠3 + m∠6 + m∠12) = 360 - (78 + 142 + 102) = 38°
m∠13 = 38°
m∠15 = 38°
m∠14 = m∠16 = 180 - m∠15 = 180 - 38° = 142°
m∠14 = 142°
m∠16 = 142°